Alternative Options for Complex, Recurrent Pain States Using Cannabinoids, Psilocybin, and Ketamine: A Narrative Review of Clinical Evidence - Amber N. Edinoff; Juliana M. Fort; Christina Singh; Sarah E. Wagner; Jessica R. Rodriguez; Catherine A. Johnson; Elyse M. Cornett; Kevin S. Murnane; Adam M. Kaye; Alan D. Kaye (MDPI AG, 2022)
With emerging information about the potential for morbidity and reduced life expectancy with long-term use of opioids, it is logical to evaluate nonopioid analgesic treatments to manage pain states. Combinations of drugs can provide additive and/or synergistic effects that can benefit the management of pain states. In this regard, tetrahydrocannabinol (THC) and cannabidiol (CBD) modulate nociceptive signals and have been studied for chronic pain treatment. Psilocybin, commonly known as "magic mushrooms", works at the serotonin receptor, 5-HT2A. Psilocybin has been found in current studies to help with migraines since it has a tryptamine structure and works similarly to triptans. Psilocybin also has the potential for use in chronic pain treatment. However, the studies that have looked at alternative plant-based medications such as THC, CBD, and psilocybin have been small in terms of their sample size and may not consider the demographic or genetic differences in the population because of their small sample sizes. At present, it is unclear whether the effects reported in these studies translate to the general population or even are significant. In summary, additional studies are warranted to evaluate chronic pain management with alternative and combinations of medications in the treatment of chronic pain.